(sin(4x) - sin(8x)) / (cos(4x) - cos(8x)) = -cot(6x)

(sin(4x) - sin(8x)) / (cos(4x) - cos(8x)) = -cot(6x)

Prove that cos^2 2x - cos^2 6x = sin 4x. sin 8x // trigonometric functions // Maths // त्रिकोणमितПодробнее

Prove that cos^2 2x - cos^2 6x = sin 4x. sin 8x // trigonometric functions // Maths // त्रिकोणमित

cos^2 2x - cos^2 6x = sin 4x sin 8xПодробнее

cos^2 2x - cos^2 6x = sin 4x sin 8x

Prove cos^2(2x) - cos^2(6x) = sin 4x sin 8xПодробнее

Prove cos^2(2x) - cos^2(6x) = sin 4x sin 8x

Prove that `(" sin 8x cos x- sin 6x cos 3x")/(" cos 2x cos x - sin 4x sin 3x")= " tan " 2x`Подробнее

Prove that `(' sin 8x cos x- sin 6x cos 3x')/(' cos 2x cos x - sin 4x sin 3x')= ' tan ' 2x`

Prove that: `cos^2 2x- cos^2 6x= sin 4x sin 8x`Подробнее

Prove that: `cos^2 2x- cos^2 6x= sin 4x sin 8x`

(cos(4x) - cos(8x)) / (cos(4x) + cos(8x)) = tan(2x) * tan(6x)Подробнее

(cos(4x) - cos(8x)) / (cos(4x) + cos(8x)) = tan(2x) * tan(6x)

(sin(4x) + sin(8x)) / sin(4x) - sin(8x)) = - tan(6x) / tan(2x)Подробнее

(sin(4x) + sin(8x)) / sin(4x) - sin(8x)) = - tan(6x) / tan(2x)

Популярное